Architecture of Care with Female Leadership: Animal Shelter Design in Puerto Cortés as a Territorial Equity Strategy - Ochoa Perdomo, Valery Anayansi; Rodriguez Mancias, Alizon Yuruany; Portillo Milla, Sofia Rachel (LACCEI, 2025)
This article presents the participatory architectural design of an animal shelter for abandoned animals in Puerto Cortés, Honduras, with a focus on sustainability, animal welfare, and female leadership. Through a technical, territorial, and social diagnosis of the PROA shelter, the central role of women in the community-based management of animal care was evidenced, as well as the need for inclusive, resilient, and bioclimatic infrastructure. The design proposal incorporates universal design criteria, the use of local materials, biophilic strategies, and adaptation to the physical and socio-cultural context. The project aligns its approach with Sustainable Development Goals 5 and 11, promoting gender equality, urban resilience, and citizen participation. Furthermore, it stands out as a transformative educational experience by integrating engineering, empathy, and gender perspective.